Accounting for specific failure criteria in the slip-line method for plane strain problems. Issue 2 (8th May 2017) - Lagioia, R.; Panteghini, A.
Abstract : This paper presents an approach to use the method of characteristics in plane strain problems with failure criteria other than the Mohr–Coulomb and Tresca. Although the method is of general validity, an instance of application is presented for the evaluation of the vertical plastic collapse load of a rigid shallow strip footing resting on a purely frictional material with no lateral surcharge. A comparison with results from finite-element analyses confirms the correctness of the approach.